Acute bout of exercise downregulates thioredoxin‐interacting protein expression in rat contracting skeletal muscles. Issue 11 (31st May 2020) - Ra, Song‐Gyu; Kawamoto, Emi; Koshinaka, Keiichi; Iwabe, Maiko; Tomiga, Yuki; Iizawa, Hiroki; Honda, Hiroki; Higaki, Yasuki; Kawanaka, Kentaro
Abstract: We previously reported that in rat skeletal muscle, disuse (i.e., decreased muscle contractile activity) rapidly increases thioredoxin‐interacting protein (TXNIP), which is implicated in the reduced glucose uptake. Accordingly, we sought herein to (a) determine the effect of exercise (i.e., increased muscle contractile activity) on muscle TXNIP protein expression, and (b) elucidate the mechanisms underlying the changes of TXNIP protein expression in response to exercise. Rat epitrochlearis and soleus muscles were dissected out after an acute bout of 3‐hr swimming (without weight loading) or 3‐hr treadmill running (15% grade at 9m/min). In a separate protocol, the isolated epitrochlearis and soleus muscles were incubated for 3 hr with AMP‐dependent protein kinase activator AICAR. Immediately after the cessation of the 3‐hr swimming, the TXNIP protein was decreased in epitrochlearis but not in soleus muscle. Conversely, 3‐hr treadmill running decreased the TXNIP protein in soleus but not in epitrochlearis muscle. TXNIP protein was decreased concomitantly with reduced postexercise muscle glycogen, showing that a decrease in TXNIP protein expression occurs in muscles that are recruited during exercise. In addition, 3‐hr incubation with AICAR decreased TXNIP protein in both isolated epitrochlearis and soleus muscles. Our results suggest that (a) an acute bout of exercise downregulates TXNIP protein expression in rat contracting skeletal muscles, and (b) the reduction in TXNIP protein expression in contracting muscles is probably mediated by AMPK activation, at least in part. Abstract : Our present findings suggest that (1) increased muscle contractile activity acutely downregulates TXNIP protein expression in rat skeletal muscles, and (2) the reduction in TXNIP protein expression in contracting muscles is probably mediated by AMPK activation, at least in part.